Efficacy and safety of aclidinium bromide in patients with COPD: A phase 3 randomized clinical trial in a Korean population. Issue 8 (15th September 2015) - Lee, Sang Haak; Lee, Jongmin; Yoo, Kwang Ha; Uh, Soo‐Taek; Park, Myung Jae; Lee, Sang Yeub; Kim, Jae Yeol; Kim, Deog Kyeom; Kim, Seung Joon; Lee, Kwan Ho; Yoo, Chul‐Gyu
Abstract Background and objective Aclidinium bromide ('aclidinium') is a novel, inhaled long‐acting muscarinic antagonist. Therapeutic effects of aclidinium on chronic obstructive pulmonary disease (COPD) have been demonstrated in Caucasian populations in several clinical trials. This was a randomized, double‐blind, multi‐centre phase‐3 clinical trial to evaluate the efficacy and safety of aclidinium in a Korean population. Methods A total of 263 Korean patients with moderate‐to‐severe COPD were randomized to receive aclidinium (400 μg, bd) (Genuai) or placebo via a dry‐powder inhaler. The primary end point was change in trough forced expiratory volume in one second (FEV1) at 12 weeks. Other lung function measurements, COPD exacerbation, health status (St George's Respiratory Questionnaire (SGRQ), dyspnoea (Transition Dyspnea Index (TDI) and safety were assessed throughout the study period. Results A significant improvement in trough FEV1 from baseline was shown with aclidinium compared with the placebo (0.126 L, P < 0.0001). Significant improvements were also demonstrated in peak FEV1 (0.190 L, P < 0.0001), SGRQ and TDI. Furthermore, aclidinium significantly reduced the prevalence of exacerbations (aclidinium, 5.4%; placebo, 15.6%, P < 0.05), and the duration of exacerbations was shorter compared with placebo (rate ratio: 0.27; P < 0.05). Aclidinium (400 μg) was well tolerated and the prevalence of adverse events was comparable with the placebo. Conclusions Inhaled aclidinium (400 μg) was shown to be safe and efficacious in Korean patients with moderate‐to‐severe COPD. Clinical trial registration: NCT01636401 at Clinicaltrials.gov